2010
DOI: 10.1074/jbc.m110.151688
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Inactivation of Peroxisome Proliferator-activated Receptor γ Coactivator 1α (PGC-1α) Protects Mice from Diet-induced Obesity and Leads to Degenerative Lesions

Abstract: Peroxisome proliferator-activated receptor ␥ coactivator 1␣ (PGC-1␣) is a transcriptional coactivator that regulates diverse aspects of energy metabolism in peripheral tissues. Mice deficient in PGC-1␣ have elevated metabolic rate and are resistant to diet-induced obesity. However, it remains unknown whether this alteration in energy balance is due to the action of PGC-1␣ in peripheral tissues or the central nervous system. In this study, we generated neuronal PGC-1␣ knock-out mice (B␣KO) using calcium/calmodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 59 publications
10
58
2
1
Order By: Relevance
“…It has been recently shown that genetic ablation of PGC-1␣ leads to impaired induction of orexigenic peptides, such as agouti-related protein (AgRP) and neuropeptide Y (NPY), under fasting conditions (Ma et al, 2010). These results are consistent with the idea that PGC-1␣ coordinates the expression of hypothalamic neuropeptides to cope with changes in energy levels in the body (Coppari et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It has been recently shown that genetic ablation of PGC-1␣ leads to impaired induction of orexigenic peptides, such as agouti-related protein (AgRP) and neuropeptide Y (NPY), under fasting conditions (Ma et al, 2010). These results are consistent with the idea that PGC-1␣ coordinates the expression of hypothalamic neuropeptides to cope with changes in energy levels in the body (Coppari et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, knock-out of the oxytocin peptide causes increased intake of animals' selected diets (Amico et al, 2005;Kasahara et al, 2007;Miedlar et al, 2007). Similarly, neuronal inactivation of PGC-1␣ leads to increased food intake (Ma et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The finding, however, that some vacuoles were observed closely attached to and partly encompassed by neuronal structures in MAP-2 and SMI-32 stainings suggests that at least a small proportion of vacuoles within the neuropil can be of neuronal origin, and that the mechanisms which lead to excessive intracellular membrane-bound fluid accumulation may affect different cell-types within the CNS, though to different extents. This hypothesis is supported by the report on CNS vacuoles observed also in neuron-specific PGC-1α knockout mice [25].…”
Section: Discussionsupporting
confidence: 76%
“…Neuroprotection through PGC-1 was shown in the contexts of oxidative stress and amyotrophic lateral sclerosis whereas neurodegeneration is associated with a loss of PGC-1 in various disorders including Huntington´s and Alzheimer´s disease [85,[130][131][132]. Consistently, global and brain-specific deletion models of PGC-1 exhibit striatal degenerative lesions and increased susceptibility for other neurodegenerative events [80,133].…”
Section: Other Organ-specific Functions Of Pgc-1 Coactivatorsmentioning
confidence: 62%